2021
DOI: 10.1007/s11126-020-09871-x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Esketamine for the Treatment of Major Depression Disorder: Findings from Randomized Controlled Trials

Abstract: Esketamine is a promising drug which can induce antidepressant effects in Major Depression Disorder (MDD). Several randomized controlled trials (RCTs) have been implemented to assess the efficacy and safety of esketamine for the treatment of MDD. Therefore, we carried out a meta-analysis to assess adverse effect profiles of esketamine for the treatment of MDD. We searched RCTs which were implemented from January 2010 to June 2020 by searching PubMed, Embase and Cochrane Library databases. Finally, four RCTs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…8,9,21,22 Several studies have examined the side effects associated with the intake of esketamine. 21,23,24 Our patients experienced mild and transient side effects, mainly in the first hour after the infusion and during the induction phase. Side effects became less frequent as the treatment continued.…”
Section: Discussionmentioning
confidence: 88%
“…8,9,21,22 Several studies have examined the side effects associated with the intake of esketamine. 21,23,24 Our patients experienced mild and transient side effects, mainly in the first hour after the infusion and during the induction phase. Side effects became less frequent as the treatment continued.…”
Section: Discussionmentioning
confidence: 88%
“…The meta-analysis by Yang et al. ( 82 ) found an overall relative risk of developing dissociation of 4.54 ( p <.00001) among patients using esketamine when compared with placebo group. This value resulted almost twice (RR: 8.06, p <.00001) in the subgroup taking the dosage of 56 mg.…”
Section: Results From the Narrative Clinical Reviewmentioning
confidence: 99%
“…It encompasses depersonalization, derealization, illusions and distortion of time, which may be experienced within a few hours and mostly at a non-severe degree by 11.1-31.4% of people treated with esketamine (28). The metaanalysis by Yang et al (82) found an overall relative risk of developing dissociation of 4.54 (p<.00001) among patients using esketamine when compared with placebo group. This value resulted almost twice (RR: 8.06, p<.00001) in the subgroup taking the dosage of 56 mg.…”
Section: Myth 6: Patient Treated With Esketamine Will Definitely Expe...mentioning
confidence: 99%
“…However, the persistence of the antidepressant effect in the medium and long term is a topic of debate in the literature. Some studies have found that the improvement observed during the induction phase with esketamine is maintained during the maintenance phase [ 71 ], while others report that the benefits may not be as consistent over time [ 78 , 79 ]. These discrepancies may be due to differences in study design and the heterogeneity of the patient sample, highlighting the need for more research in this area.…”
Section: Treatment Options For Treatment-resistant Depressionmentioning
confidence: 99%